FMRF‐NH2‐related neuropeptides in Biomphalaria spp., intermediate hosts for schistosomiasis: Precursor organization and immunohistochemical localization. Issue 13 (11th June 2021) - Rolón‐Martínez, Solymar; Habib, Mohamed R.; Mansour, Tamer A.; Díaz‐Ríos, Manuel; Rosenthal, Joshua J. C.; Zhou, Xiao‐Nong; Croll, Roger P.; Miller, Mark W.
Abstract: Freshwater snails of the genus Biomphalaria serve as intermediate hosts for the digenetic trematode Schistosoma mansoni, the etiological agent for the most widespread form of intestinal schistosomiasis. As neuropeptide signaling in host snails can be altered by trematode infection, a neural transcriptomics approach was undertaken to identify peptide precursors in Biomphalaria glabrata, the major intermediate host for S . mansoni in the Western Hemisphere. Three transcripts that encode peptides belonging to the FMRF‐NH2 ‐related peptide (FaRP) family were identified in B . glabrata . One transcript encoded a precursor polypeptide ( Bgl‐FaRP1 ; 292 amino acids) that included eight copies of the tetrapeptide FMRF‐NH2 and single copies of FIRF‐NH2, FLRF‐NH2, and pQFYRI‐NH2 . The second transcript encoded a precursor ( Bgl‐FaRP2 ; 347 amino acids) that comprised 14 copies of the heptapeptide GDPFLRF‐NH2 and 1 copy of SKPYMRF‐NH2 . The precursor encoded by the third transcript ( Bgl‐FaRP3 ; 287 amino acids) recapitulated Bgl‐FaRP2 but lacked the full SKPYMRF‐NH2 peptide. The three precursors shared a common signal peptide, suggesting a genomic organization described previously in gastropods. Immunohistochemical studies were performed on the nervous systems of B . glabrata and B . alexandrina, a major intermediate host for S . mansoni in Egypt. FMRF‐NH2 ‐like immunoreactive (FMRF‐NH2 ‐li) neurons were located in regions of the central nervous system associated with reproduction, feeding, and cardiorespiration. Antisera raised against non‐FMRF‐NH2 peptides present in the tetrapeptide and heptapeptide precursors labeled independent subsets of the FMRF‐NH2 ‐li neurons. This study supports the participation of FMRF‐NH2 ‐related neuropeptides in the regulation of vital physiological and behavioral systems that are altered by parasitism in Biomphalaria . Abstract : Freshwater snails of the genus Biomphalaria serve as intermediate hosts for the digenetic trematode Schistosoma mansoni, the etiological agent for the most widespread fo rm of intestinal schistosomiasis. A neural transcriptomics approach was undertaken to identify peptide precursors in Biomphalaria glabrata, the major intermediate host for S . mansoni in the Western Hemisphere. Three precursors encoding FMRF‐NH2 ‐related peptides were characterized and localized to specific neurons and cell groups in the central nervous system. The image shows the ventral lobe, a cluster of neurons that controls male reproductive behavior in snails.